Characteristics of Opioid-Using Pregnant Women Who Accept or Refuse Participation in a Clinical Trial: Screening Results from the MOTHER Study - Stine, Susan M. (2009)
BACKGROUND: Although concerns arise about the generalizability of results from Randomized Controlled Trials (RCTs), few studies systematically examine this issue. OBJECTIVES: This study compared the characteristics of 427 opioid-using pregnant women who did (n =208) and did not consent (n=219) to enrollment in a multi-center clinical trial of agonist medications (i.e., the MOTHER study). METHODS: Logistic regression models were used to compare consenters and non-consenters to examine the effect of screening variables on the likelihood of consenting. RESULTS: Of nine characteristics examined, most differences did not reach statistical significance. Consenting participants were less likely than non-consenting women to be currently enrolled in a methadone maintenance program (74.5% vs. 84.5%, p=.01). CONCLUSION AND SCIENTIFIC SIGNIFICANCE: These data show that the recruited sample of drug-dependent pregnant women enrolled in an intensive RCT is representative of the larger population of treated opioid-dependent patients and supports the generalizability of randomized controlled trials in this population.